ANALISIS PEMBANGUNAN DAN POTENSI PASAR - Asrudi Asrudi; Wayrohi Meilvidiri; Siti Nafisah Azis (Faculty Of Economics and Business, Musamus University, 2019)
The growth in the population of each region will present its own problems, especially the level of complexity in the certain community activities. It can also be seen in the form of the traditional markets that have a role as a place for the purchase and sale of commodities, and to meet the needs of the community. The purpose of this study is to measure the potential for development of the Fagogoru market. Analysis is conducted using three methods, namely the market share method, the potential market, and the growth ratio model (MRP). The results of this study showed that the potential of the Fagogoru market had the considerable potential, where the results of the analysis of the estimated market potential (Market Potential) of Central Halmahera Regency reached Rp 1.450 trillion, while in the Weda sub-district area was around Rp 344,3 billion. This considerable potential was supported by the adequate agricultural sector conditions. Keywords: Fagogoru market, market share, market potential